2011
DOI: 10.1007/s11740-011-0348-4
|View full text |Cite
|
Sign up to set email alerts
|

A voxel-based kinematic simulation model for force analyses of complex milling operations such as wobble milling

Abstract: Mechanical machining of fiber reinforced plastics poses special challenges due to the heterogeneous and anisotropic material composition. Process strategies for the generation of drill holes, which aim at directing the resultant process forces toward the center of the workpiece, have been shown to obtain good machining results with less process induced damage. However, these strategies (e.g. wobble milling) might involve complex multiaxial tool movements and are thus very difficult to analyze and optimize. A v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…They stated that only tool inclination angle had a significant influence on effective force angle as compared to feed rate and cutting-edge radius. In the other study of Schulze et al (Schulze et al, , 2012, machining-induced damage was reduced by adopting complex machining strategies (five-axial advanced machining) in comparison to conventional drilling. In the recent article of Csongor Pereszlai & Norbert Geier (Pereszlai & Geier, 2020), comparing the wobble milling, helical milling with conventional drilling on CFRP, authors stated that wobble milling technique was more effective in minimizing the amount of uncut fibers.…”
Section: Special Tool Pathsmentioning
confidence: 99%
“…They stated that only tool inclination angle had a significant influence on effective force angle as compared to feed rate and cutting-edge radius. In the other study of Schulze et al (Schulze et al, , 2012, machining-induced damage was reduced by adopting complex machining strategies (five-axial advanced machining) in comparison to conventional drilling. In the recent article of Csongor Pereszlai & Norbert Geier (Pereszlai & Geier, 2020), comparing the wobble milling, helical milling with conventional drilling on CFRP, authors stated that wobble milling technique was more effective in minimizing the amount of uncut fibers.…”
Section: Special Tool Pathsmentioning
confidence: 99%
“…Schulze and Beke [52] investigated the impacts of process and workpiece parameterssuch as feed, tool inclination, tool spiral angle and cutting-edge radiuson resultant machining force vectors. They also showed that wobble milling is insensitive to tool wear and they developed a mechanistic model to calculate chip geometry and specific forces in the scope of their study [51]. In addition, they figured out that during wobble milling the top laminated layers of CFRPs can be machined with the resulting process force vector directed towards the centre of the workpiece.…”
Section: Wobble Milling Of Cfrpsmentioning
confidence: 99%
“…12 Impact of drilling strategies and cutting tools on the circularity errors of machined holes laminated layers of the composite. The burr area was expected to be larger in drilling operations than in the case of wobble or helical milling operations [50][51][52], because the axial cutting force (which bends the fibres at the exit of the hole) is higher during drilling.…”
Section: Impacts Caused By Tool Geometry and Drilling Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These may include (i) removing material build-up in the dividing plane of the laminating tool, (ii) removing excess material from the flange of the laminating tools, (iii) smoothing the mating surfaces of the laminated composites, and (iv) making holes for assembly of components [7][8][9]. Typically, these post-manufacturing needs are met by various machining techniques, like conventional drilling, helical milling, tilted helical milling, wobble milling, side milling, or edge trimming [6,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%